2012
DOI: 10.1097/phm.0b013e31823c7507
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Visual and Auditory Cues on Freezing of Gait in Patients with Parkinson Disease

Abstract: This study suggests that gait training using visual and auditory cues can improve PDF patient gait and that auditory cues enhance gait in PDNF patients with hypokinetic gait patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 28 publications
4
90
0
1
Order By: Relevance
“…High-contrast, transverse line visual cues on the floor have been found to improve stride length and velocity, among other measures, in patients with PD in several trials, one of which also demonstrated reduced FOG episodes [11,[13][14][15][16][17][18]. Another of these trials demonstrated similar benefits with a laser beam visual cue [15].…”
Section: Freezing Of Gait (Fog) Is a Disabling Phenomenon That Affectsupporting
confidence: 48%
See 1 more Smart Citation
“…High-contrast, transverse line visual cues on the floor have been found to improve stride length and velocity, among other measures, in patients with PD in several trials, one of which also demonstrated reduced FOG episodes [11,[13][14][15][16][17][18]. Another of these trials demonstrated similar benefits with a laser beam visual cue [15].…”
Section: Freezing Of Gait (Fog) Is a Disabling Phenomenon That Affectsupporting
confidence: 48%
“…Jiang and Norman reported 14 patients with PD, 7 with FOG, who demonstrated increased first and second stride lengths, greater push-off force, and higher velocity with highcontrast transverse line visual cues on the floor [11]. Applying these observations to FOG specifically, Lee et al recently published a trial in which white stripes on the floor significantly increased velocity and stride length and decreased cadence and freezing episodes in PD patients with FOG [16]. Dunne et al reported on three PD subjects who were extensively trained in the use of a visual cue to break freezing and whose FOG was thereafter effectively aborted using an upturned walking stick [10].…”
Section: Discussionmentioning
confidence: 91%
“…Findings from this current study and from previous reports suggest that gait changes in FGD have similar characteristics to PD gait. The use of cues and attentional strategies has been shown to be effective in improving stride length and cadence in Parkinson's disease [30]. Future studies are required to investigate the effectiveness of similar strategies to improve gait in FGD.…”
Section: Discussionmentioning
confidence: 98%
“…Several clinical trials indicate cueing therapy-induced improvements in walking speed, step length, and frequency in PD. [43][44][45][46] From a neuroanatomical perspective, enhanced activation of the premotor cortex seems to be relevant for the improvement of motor performance induced by cueing therapy. 47 Thus, Costa-Ribeiro et al 29 investigated the effects of tDCS combined with cued gait training (CGT) on functional mobility in patients with PD.…”
Section: Combining Tdcs With Cueing And/ or Physical Trainingmentioning
confidence: 99%